Conversion recovery device of formic acid solvent in metronidazole production process - WEI LIAN'AN; WEI MINGCHANG; CAI MIN; BAN ZHIHUA (2019)
The invention discloses a conversion recovery device of a formic acid solvent in a metronidazole production process and belongs to the technical field of disposal of wastewater containing formic acidin metronidazole production. The conversion recovery device consists of a reaction kettle, a condenser, a methanol storage device, a neutralization reaction kettle, a tail liquid storage tank and a methyl formate collection tank, wherein a process of esterifying formic acid and methanol, performing heating for reflux and conducting distillation to collect methyl formate is adopted. In order to solve a serious problem that the emission of industrial formic acid wastewater generated in a synthesis process of a bulk drug 2-methyl-5-nitroimidazole-1-ethanol exceeds the standards, the theoretical basis of conversion and recovery of the industrial formic acid wastewater is analyzed, correspondingly the industrial formic acid wastewater is converted into a methyl formate finished product with certain concentration and so